Penerapan Pemberian Terapi Musik Klasik Pada Lansia dengan Gangguan Tidur di Rumah Lansia Bhakti Kasih Siti Anna Pangkalpinang (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Sleep disorders experienced by older people are difficulty falling asleep, maintaining sleep and difficulty returning to sleep after waking up at night, thus affecting sleep quality. One therapy that can improve sleep quality is music therapy. Music therapy is a stimulation that has a slow rhythm, a stable rhythm pattern that stimulates relaxation of the parasympathetic nervous system, thereby creating a relaxed atmosphere that supports increased sleep duration The researcher aims to provide an overview of nursing care for  the elderly with sleep disordes. The design usedin this nursing final scientifik paper ia a case study with clasical musik  therapi intervention. Therer respondent parcipated, and the intervention was conducted from Desember 20-23, art the Bhakti Kasih Siti Anna Pangkalpinang Elderly Home: After Four consecutive days of classical  musik therapi, thr three elderly individuals experienced  changes  in their PSQI scoret at the final meeting: Ms. E’s score increased from 17 to 13, Mrs. A’s ckore decreased from 19 to 12, and Mrs. M’s score decreased from 16 to 13. Classical musik therapi is effective in treating sleep disorders. The implementation of EBP is expected to provide additional information  regarding the provision of musik therapi to elderly individuals experiencing sleep disorders.